2018
DOI: 10.15835/nbha46110846
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Physiological Characteristics of Lettuce (Lactuca sativa L.) and Rocket (Eruca sativa Mill.) Plants Cultivated under Photovoltaic Panels

Abstract: Energy demand of greenhouses is an important factor for their economics and photovoltaics can be considered an alternative solution to cover their electrical and heating needs. On the other hand, plants cultivated under different solar radiation intensities usually appear different physiological adaptations. The objective of this research was to investigate the effect of photovoltaic panels' induced partial shading on growth and physiological characteristics of lettuce (Lactuca sativa L.) and rocket (Eruca sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
18
0
4
Order By: Relevance
“…In a previous study, based on a comparison among different leafy vegetable species, Wolff and Coltman [37] highlighted that the crops positively benefited from shading up to 30%-47%, with lettuce showing a 36% yield increase and head and Chinese cabbage a 23% and 21% augmentation, respectively. Kavga et al [38] reported that, in a comparison between lettuce and rocket crops grown under a 25% shading net, only the rocket crop showed a yield loss up to 50% compared to the unshaded control. In contrast, Ilić et al [30] recorded an increased yield of Lactuca sativa L. grown under different 50% shading nets; specifically, the leaf area index, the total fresh weight, the leaf number per plant and stem length increased under shading in comparison with the unshaded control, suggesting the existence of a light-dependent mechanism by which the plants regulate the leaf size.…”
Section: Plant Growth and Yieldmentioning
confidence: 99%
“…In a previous study, based on a comparison among different leafy vegetable species, Wolff and Coltman [37] highlighted that the crops positively benefited from shading up to 30%-47%, with lettuce showing a 36% yield increase and head and Chinese cabbage a 23% and 21% augmentation, respectively. Kavga et al [38] reported that, in a comparison between lettuce and rocket crops grown under a 25% shading net, only the rocket crop showed a yield loss up to 50% compared to the unshaded control. In contrast, Ilić et al [30] recorded an increased yield of Lactuca sativa L. grown under different 50% shading nets; specifically, the leaf area index, the total fresh weight, the leaf number per plant and stem length increased under shading in comparison with the unshaded control, suggesting the existence of a light-dependent mechanism by which the plants regulate the leaf size.…”
Section: Plant Growth and Yieldmentioning
confidence: 99%
“…Klaring and Krumbein [162] in Germany reported that shading greenhouses with PV reduced growth and yield of tomato plants, but without compromising fruit quality. In Greece, studies by Kavga et al [163] and Trypanagnostopoulos et al [164] revealed that lettuces grown in 20% PV-shaded greenhouses were of comparable quality to the lettuce grown in open roof greenhouses.…”
Section: Passive Cooling Technologies: Shading and Reflectionmentioning
confidence: 98%
“…Trypanagnostopoulos et al [89,93] explained that the use of photovoltaic panels in a lettuce crop produced a 20% shading of the greenhouse, and plant growth was the same as that of the reference greenhouse, without photovoltaic panels on the roof.…”
Section: Photovoltaic Modules In Greenhousesmentioning
confidence: 99%